Integrating post-validation surveillance of lymphatic filariasis with the WHO STEPwise approach to non-communicable disease risk factor surveillance in Niue, a study protocol. - Adam T Craig; Harriet Lawford; Grizelda Mokoia; Minerva Ikimau; Peter Fetaui; Tonia Marqardt; Colleen L Lau (PLoS ONE)
Background Lymphatic filariasis (LF), a mosquito-borne parasitic disease caused by three species of filarial worms, was first detected in Niue, a small Pacific Island nation of approximately 1,600 people, in 1954. After extensive efforts involving multiple rounds of Mass Drug Administration, Niue was validated by the World Health Organization (WHO) as having e4liminated LF as a public health problem in 2016. However, no surveillance has been conducted since validation to confirm infection rates have remained below WHO's elimination threshold. WHO has encouraged an integrated approach to disease surveillance and integrating LF post-validation surveillance (PVS) with existing surveys is an anticipated recommendation of the upcoming WHO LF-PVS guidelines. This paper describes a protocol for the implementation of an integrated approach to LF-PVS in Niue as cost-efficient and operationally feasible means of monitoring the disease in the population. Methods The LF-PVS will be implemented as part of a planned national population-based WHO STEPwise approach to non-communicable disease (NCD) risk factor surveillance (STEPS) in Niue. Integration between the LF-PVS and STEPS will occur at multiple points, including during pre-survey community awareness raising and engagement, when obtaining informed consent, during the collection of demographics, risk factor, and location data, and when collecting finger-prick blood samples (for glucose as part of the STEPS survey and LF as part of the LF-PVS). The primary outcome measure for LF transmission will be antigen positivity. Microfilaria slides will be prepared for any antigen-positive cases. Dried blood spots will be prepared for all participants for Multiplex Bead Assays-based analysis to detect anti-filarial antibodies. We estimate a total sample size of 1,062 participants aged 15-69, representing approximately 66% of the population. Conclusions The results of this study will provide insight into the status of LF in Niue and evaluate the advantages, challenges, and opportunities offered by integrated approaches to disease surveillance.